2002
DOI: 10.1177/229255030201000206
|View full text |Cite
|
Sign up to set email alerts
|

Reston: A Plastic Surgeon's Dream Material

Abstract: Reston foam is a polyurethane ether polymer that has many attractive features for use by plastic surgeons. In the present paper, these features are addressed and clinical examples are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…13 Reston (3M Company, Minn.) is a polyurethane self-adhering foam which has been in use for several decades as a bolster. [14][15][16] In vitro studies, first performed in the 1980s, demonstrated that Reston provides uniform and physiologic pressure over the skin graft sites. 14 This benefit, in addition to the porosity of the material which helps in eliminating drainage, makes it an ideal bolster for recipient sites.…”
Section: Ideas and Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Reston (3M Company, Minn.) is a polyurethane self-adhering foam which has been in use for several decades as a bolster. [14][15][16] In vitro studies, first performed in the 1980s, demonstrated that Reston provides uniform and physiologic pressure over the skin graft sites. 14 This benefit, in addition to the porosity of the material which helps in eliminating drainage, makes it an ideal bolster for recipient sites.…”
Section: Ideas and Innovationsmentioning
confidence: 99%
“… 14 , 15 Reston is also relatively inexpensive, costing less than $3 per 20 × 30 cm sheet. 16 It is usually held in place by staples to the skin edge, tie-over methods, or other adhesives, with consistently successful results. 14 , 15 , 17 , 18 However, due to the moist environment of the vulva (with significant serous drainage), the dressings often become moist 48 hours after surgery and may require replacement.…”
Section: Introductionmentioning
confidence: 99%